An Intraoral Repair Method for Chipping Fracture of a Multi-unit Fixed Zirconia Reconstruction: A Direct Dental Technique - Mesquita, Alfredo Mikail Melo; Al-Haj Husain, Nadin; Molinero-Mourelle, Pedro; Özcan, Mutlu (European Journal of Dentistry, 2021)
Fracture or chipping of veneering ceramic is one of the most frequent clinical failures in dentistry in fixed dental and implant-borne prostheses. Due to the friable nature of the ceramic material, chippings may result in an aesthetic and functional problem for the patient requiring a rapid solution. Direct repairs have been indicated for the restoration of function, aesthetics and comfort, especially in cases where the fractured prosthesis presents good adaptation and satisfactory aesthetics. This case report aims to present and discuss the techniques of the direct reveneering method, their advantages and disadvantages, as well as the importance of adhesive procedures in the success of these restorative approaches. Success in repairing the fractured area, regardless of the technique used, is fundamental to establish a strong and stable adhesion between the repaired and the fractured areas, since the longevity of the repair will depend on the quality of the interface generated.
Keywords: ceramic; chipping; reveneering; zirconia